Dynamics of Collapse of a High Building - Němec, Ivan; Juráňová, Martina; Ševčík, Ivan; Frantík, Petr; Vlk, Zbyněk (David Publishing, 2012)
This paper is a contribution to the discussion about the fall of the New York World Trade Center (WTC) towers in 2001. The differential equation of the collapse of a high building is derived by taking into account many infuences. A computer simulation of the collapse the WTC building is presented using two independent programs with parameter variations. The results of both, differential equation and computer simulation, are compared resulting correspondences. The authors consider certain probable parameters with would have lessened both the observable speed of the collapse and its extent, however uncertainty regarding the magnitudes of the parameters remains.

This paper is a contribution to the discussion about the fall of the New York World Trade Center (WTC) towers in 2001. The differential equation of the collapse of a high building is derived by taking into account many infuences. A computer simulation of the collapse the WTC building is presented using two independent programs with parameter variations. The results of both, differential equation and computer simulation, are compared resulting correspondences. The authors consider certain probable parameters with would have lessened both the observable speed of the collapse and its extent, however uncertainty regarding the magnitudes of the parameters remains.
Dynamics of Collapse of a High Building
Keywords: Dynamics; collapse; WTC (World Trade Center); Dynamics; collapse; WTC (World Trade Center)